2013
DOI: 10.1089/humc.2013.165
|View full text |Cite
|
Sign up to set email alerts
|

Safety Studies on Intravenous Administration of Oncolytic Recombinant Vesicular Stomatitis Virus in Purpose-Bred Beagle Dogs

Abstract: VSV-IFNβ-NIS is a novel recombinant oncolytic vesicular stomatitis virus (VSV) with documented efficacy and safety in preclinical murine models of cancer. To facilitate clinical translation of this promising oncolytic therapy in patients with disseminated cancer, we are utilizing a comparative oncology approach to gather data describing the safety and efficacy of systemic VSV-IFNβ-NIS administration in dogs with naturally occurring cancer. In support of this, we executed a dose-escalation study in purpose-bred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 16 publications
(22 reference statements)
1
61
0
Order By: Relevance
“…Using VSVs encoding type I and type III IFNs Several recent pre-clinical studies have shown that VSVIFNb and VSV-IFNb-NIS (additionally expresses the NIS to track virus spread) are oncoselective and safe in a variety of tumour and animal models [24,[27][28][29][30][31]. Although mice and rats continue to serve as the most commonly used animal models for VSV-based OV therapy, a recent study evaluated the safety of intravenously administered VSV-IFNb-NIS in purpose-bred beagle dogs.…”
Section: Improving Oncoselectivity and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Using VSVs encoding type I and type III IFNs Several recent pre-clinical studies have shown that VSVIFNb and VSV-IFNb-NIS (additionally expresses the NIS to track virus spread) are oncoselective and safe in a variety of tumour and animal models [24,[27][28][29][30][31]. Although mice and rats continue to serve as the most commonly used animal models for VSV-based OV therapy, a recent study evaluated the safety of intravenously administered VSV-IFNb-NIS in purpose-bred beagle dogs.…”
Section: Improving Oncoselectivity and Safetymentioning
confidence: 99%
“…dose of 10 10 TCID50 was well-tolerated by dogs. Furthermore, no infectious virus was detectable in plasma, urine or buccal swabs at any tested doses [29]. Importantly, VSV-IFNb-NIS is currently in several phase I clinical trials in the USA: against refractory solid tumours (see details at ClinicalTrials.gov trial NCT02923466), stage IV or recurrent endometrial cancer (trial NCT03120624), and relapsed or refractory multiple myeloma, acute myeloid leukemia or T-cell lymphoma (trial NCT03017820).…”
Section: Improving Oncoselectivity and Safetymentioning
confidence: 99%
“…Safety studies in research beagles before the start of the canine trial indicated that the maximal tolerated dose (MTD) in dogs is 10 10 TCID 50 (50% tissue culture infective dose) of VSV-hIFNb-NIS or VSVcIFNb-NIS. 6 At 10 · MTD (10 11 TCID 50 ), the doselimiting toxicity is severe hepatotoxicity with elevations in transaminases and prolongation of partial thromboplastin time (PTT), requiring euthanasia of the animal. Intensive pharmacokinetics studies showed a rapid increase in VSV-nucleocapsid (N) RNA in the blood from 10 min to 3 hr after virus infusion (end of acute-phase monitoring).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the virus has been administered intravenously to purpose bred research hounds where the maximal tolerated dose was determined to be 10 10 TCID 50 (dose-limiting toxicity was mildly elevated transaminases). 15 VSV-IFNβ-NIS is active against a broad spectrum of tumors of differing tissue origins and tumor response is typically not associated with significant toxicities. For example, in immunocompetent mice with large subcutaneous 5TGM1 myeloma tumors, an intravenous dose of 3 × 10 8 TCID 50 VSV-murine IFNβ-NIS can result in sustained complete remission and induction of tumorspecific memory T cells that protect the mice from new tumor cell challenge.…”
Section: Introductionmentioning
confidence: 99%